2023
DOI: 10.1039/d3nr00096f
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the intertwined: metallic to semiconducting phase transition of colloidal MoS2 nanoplatelets and nanosheets

Abstract: 2D semiconducting transition metal dichalcogenides (TMDCs) are highly promising materials for future spin- and valleytronic applications and exhibit an ultrafast response to external (optical) stimuli which is essential for optoelectronics....

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 71 publications
(100 reference statements)
1
18
0
Order By: Relevance
“…We stress that bleaches of the A, B, and C exci-tons are instantaneously formed in the reductive EMAS scans upon departing from the OCP (Figure 2) even for potentials far below the conduction band edge. The bleaching below −1.2 V is therefore not caused by band filling but rather a sign of bandgap renormalization, previously observed in TA measurements, [10,31,32] by chemical doping [33] and by spectroelectrochemistry of 3-layer, 150 nm large 2H-MoS 2 nanosheets produced by liquid-based exfoliation. [25] Briefly, upon electron injection into 2H-MoS 2 nanosheets the self-energy of the electron and hole states decreases due to many-body effects, and this decrease is typically larger for the electron states.…”
Section: Doping and Bandgap Renormalizationsupporting
confidence: 53%
See 3 more Smart Citations
“…We stress that bleaches of the A, B, and C exci-tons are instantaneously formed in the reductive EMAS scans upon departing from the OCP (Figure 2) even for potentials far below the conduction band edge. The bleaching below −1.2 V is therefore not caused by band filling but rather a sign of bandgap renormalization, previously observed in TA measurements, [10,31,32] by chemical doping [33] and by spectroelectrochemistry of 3-layer, 150 nm large 2H-MoS 2 nanosheets produced by liquid-based exfoliation. [25] Briefly, upon electron injection into 2H-MoS 2 nanosheets the self-energy of the electron and hole states decreases due to many-body effects, and this decrease is typically larger for the electron states.…”
Section: Doping and Bandgap Renormalizationsupporting
confidence: 53%
“…Synthesis of 2H-MoS 2 Nanosheets: Colloidal 2H-MoS 2 nanosheets were synthesized based on the previously reported protocol [10,11] to obtain mono and bilayers with a lateral dimension of ≈20-25 nm. The Mo-precursor was prepared by dissolving molybdenum(V)-chloride in a mixture of oleylamine and oleic acid of 10:1 by stirring inside a glovebox for 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because most of these c-TMDs show indirect band gap behavior for non-monolayer systems, there was a knowledge gap compared to those samples prepared by chemical vapor deposition (CVD) growth, where high-quality monolayers with bright PL are by now routinely obtained. , However, in the past years, several reports indicated the possibility to form monolayered c-TMDs through colloidal synthesis approaches. Frauendorf et al and Pippia et al reported on the room-temperature and cryogenic luminescence of colloidally synthesized WS 2 and MoX 2 (X = S and Se). Given the still very limited luminescence efficiency, there is clearly still a need for further optimization. Unfortunately, there is little known about the fate of charge carriers in these monolayer c-TMD systems after photoexcitation.…”
mentioning
confidence: 99%